Vitiligo Area Scoring Index and Vitiligo European Task Force assessment: reliable and responsive instruments to measure the degree of depigmentation in vitiligo. (1st February 2015) - Komen, L.; da Graça, V.; Wolkerstorfer, A.; de Rie, M.A.; Terwee, C.B.; van der Veen, J.P.W.
Summary: Background: Vitiligo is a common skin disorder causing depigmented macules that can impair a patient's quality of life. Currently, there are no standardized outcome measures to assess the degree of depigmentation. Moreover, there is limited knowledge on the measurement properties of outcome measures in vitiligo. Objectives: To assess the reliability and responsiveness of the Vitiligo Area Scoring Index (VASI) and the Vitiligo European Task Force assessment (VETFa), two well‐described clinician‐reported outcomes. Methods: We included three vitiligo patient groups. In one group of 31 patients, the interobserver reliability was assessed by three observers. In 27 patients the intraobserver reliability was assessed by two repeated measures by one of the observers. To assess the responsiveness the repigmentation was calculated after 6 months of phototherapy in 33 patients and tested against hypotheses. Results: The interobserver reliability was high for VASI [intraclass correlation coefficient (ICC) 0·93] and VETFa depigmentation (ICC 0·88). The intraobserver reliability was high for VASI (ICC 0·93) and VETFa depigmentation (ICC 0·97). The smallest detectable changes (SDCs) were 7·1% and 10·4% for interobserver reliability and 4·7% and 2·9% for intraobserver reliability in VASI and VETFa depigmentation, respectively. All four responsiveness hypotheses formulated a priori were confirmed. Conclusions: VASI and VETFa are reliable and responsive instruments to assess the degree of depigmentation in vitiligo. VASI and VETFa for depigmentation are potential instruments for vitiligo research in the future. However, for use in individual patient care, caution is needed when interpreting score changes in individual patients because of the relatively large SDC.